Impacts of vitrification on the transcriptome of human ovarian tissue in patients with gynecological cancer - Gu, Ruihuan; Ge, Naidong; Huang, Bin; Fu, Jing; Zhang, Ying; Wang, Ningyi; Xu, Yan; Li, Lu; Peng, Xiandong; Zou, Yaoyu; Sun, Yijuan; Sun, Xiaoxi (Frontiers in Genetics, 2023)
Objective: This study investigated the effects of a vitrification/warming procedure on the mRNA transcriptome of human ovarian tissues. Design: Human ovarian tissues were collected and processed through vitrification (T-group) and then subjected to RNA sequencing (RNA-seq) analysis, HE, TdT-mediated dUTP nick-end labeling (TUNEL), and real-time quantitative PCR, and the results were compared to those of the fresh group (CK). Results: A total of 12 patients, aged 15–36 years old, with a mean anti-Müllerian hormone level of 4.57 ± 3.31 ng/mL were enrolled in this study. According to the HE and TUNEL results, vitrification effectively preserved human ovarian tissue. A total of 452 significantly dysregulated genes (|log2FoldChange| > 1 and p < 0.05) were identified between the CK and T groups. Among these, 329 were upregulated and 123 were downregulated. A total of 372 genes were highly enriched for 43 pathways (p < 0.05), which were mainly related to systemic lupus erythematous, cytokine–cytokine receptor interaction, the TNF signaling pathway, and the MAPK signaling pathway. IL10, AQP7, CCL2, FSTL3, and IRF7 were significantly upregulated (p < 0.01), while IL1RN, FCGBP, VEGFA, ACTA2, and ASPN were significantly downregulated in the T-group (p < 0.05) compared to the CK group, which agreed with the results of the RNA-seq analysis. Conclusion: These results showed (for the first time to the authors’ knowledge) that vitrification can induce changes in mRNA expression in human ovarian tissues. Further molecular studies on human ovarian tissues are required to determine whether altered gene expression could result in any downstream consequences.